2019
DOI: 10.1177/1178221819833379
|View full text |Cite
|
Sign up to set email alerts
|

How Social Relationships Influence Substance Use Disorder Recovery: A Collaborative Narrative Study

Abstract: Individuals with a substance use disorder (SUD) often have fewer social support network resources than those without SUDs. This qualitative study examined the role of social relationships in achieving and maintaining stable recovery after many years of SUD. Semi-structured interviews were conducted with 18 participants, each of whom had been diagnosed with a SUD and each of whom had been abstinent for at least 5 years. A resource group of peer consultants in long-term recovery from SUDs contributed to the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 42 publications
(72 reference statements)
5
68
0
2
Order By: Relevance
“…Non-judgmental communication was the prevailing characteristic among community pharmacists who provided positive experiences for participants. This nding supports the integral role of social relations and support for the recovery and treatment retention of patients living with SUD (64,65).…”
Section: Discussionsupporting
confidence: 71%
“…Non-judgmental communication was the prevailing characteristic among community pharmacists who provided positive experiences for participants. This nding supports the integral role of social relations and support for the recovery and treatment retention of patients living with SUD (64,65).…”
Section: Discussionsupporting
confidence: 71%
“…Functional social support indicates the quality of social support received, which is important for approaches in decreasing SUD. Caring, positive relationships that include informational support and promotion of self-efficacy are linked to reduced substance use initiation [21,[52][53][54], and higher functional social support has been found to increase efficacy of substance use treatment interventions and identified as an indicator of entry and retention in treatment [55][56][57]. Due to the cross-sectional nature of our data, we are unable to determine whether higher social provision results in lower SUD or if the presence of SUD results in lower social provision due to loss of support resources related to substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Family support, especially for adolescents in long term residential programs has been proven to be necessary for successful recovery from addiction [ 66 ]. Studies have also showed that having a strong social and family resource improves the chances of addiction recovery [ 67 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…Family support, especially for adolescents in long term residential programs has been proven to be necessary for successful recovery from addiction [66]. Studies have also showed that having a strong social and family resource improves the chances of addiction recovery [67][68][69][70]. Self-development efforts encompassing activities that lead to mental and physical well-being, such as regular exercise, meditation, and yoga have been observed to help heal the body and mind [71,72].…”
Section: The Sem Model For Recoverymentioning
confidence: 99%